1998
DOI: 10.1074/jbc.273.28.17871
|View full text |Cite
|
Sign up to set email alerts
|

Nitroxides Tempol and Tempo Induce Divergent Signal Transduction Pathways in MDA-MB 231 Breast Cancer Cells

Abstract: Tempol and tempo are stable free radical nitroxides that possess antioxidant properties. In this study, we examined the effects of these compounds on components of the mitogen-activated protein kinase signal transduction cascade. Tempo treatment (15 min) of MDA-MB 231 human breast cancer cells resulted in significant levels of tyrosine phosphorylation of several as yet unidentified proteins compared with equimolar concentration of tempol (10 mM). Both compounds caused tyrosine phosphorylation and activation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
38
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 76 publications
3
38
0
Order By: Relevance
“…20% (Table 1), and 2.3 mM resulting in essentially no growth of TK6 cells (Table 2). These result are consistent with a time course analysis of TEMPO cytotoxicity in different types of tumor cells, which indicated that TEMPO treatment resulted in a > 50% decrease in the number of viable cells and a steady increase in apoptosis during the first 2 h of exposure, followed by a considerable increase in necrosis by 3 h (Suy et al, 1998). A 24 h treatment with TEMPO was cytotoxic to HaCaT human keratinocytes, producing an IC 50 of 2.66 mM using the amido-black-assay (Kroll et al, 1999).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…20% (Table 1), and 2.3 mM resulting in essentially no growth of TK6 cells (Table 2). These result are consistent with a time course analysis of TEMPO cytotoxicity in different types of tumor cells, which indicated that TEMPO treatment resulted in a > 50% decrease in the number of viable cells and a steady increase in apoptosis during the first 2 h of exposure, followed by a considerable increase in necrosis by 3 h (Suy et al, 1998). A 24 h treatment with TEMPO was cytotoxic to HaCaT human keratinocytes, producing an IC 50 of 2.66 mM using the amido-black-assay (Kroll et al, 1999).…”
Section: Discussionsupporting
confidence: 76%
“…A 24 h treatment with TEMPO was cytotoxic to HaCaT human keratinocytes, producing an IC 50 of 2.66 mM using the amido-black-assay (Kroll et al, 1999). It has been reported that TEMPO is approximately 200 times more lipophilic than its derivative 4-hydroxy-2,2,6,6-tetramethylpiperidine 1-oxyl (4-hydroxy-TEMPO) (Suy et al, 1998), which may facilitate its accumulation in the cell membrane and potentiate its cellular toxicity. In addition, TEMPO is a unique thermosensitizer that synergistically induces cell death when 5-10 mM TEMPO is presented during heating at 44°C in U937 leukemic cells and results in Bax activation and mitochondrial outer membrane permeabilization (Zhao et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, 5-125 may act as an SOD-mimetic and dismutate superoxide radicals to hydrogen peroxide (24,25). Finally, Suy et al (44) reported that the nontargeted nitroxide, TEMPOL, stimulated the extra cellular signal-regulated kinase (ERK) signaling pathway, which primarily promotes growth and proliferation/survival.…”
Section: Discussionmentioning
confidence: 99%
“…Nitroxides provide protection in cells and tissues against diverse types of insult, such as exposure to superoxide and hydrogen peroxide, by directly scavenging the ROS (31). In addition to protection by radical scavenging, nitroxides also evoke cellular responses such as cell signaling -specific pathways (32,33). The ability to trigger cell signaling -specific pathways has been postulated to support possible antitumor effects of nitroxides in vivo (34,35).…”
Section: Discussionmentioning
confidence: 99%